On the Role of Psychological Health and Buoyancy in EFL Teachers' Professional Commitment - Li, Manman (Frontiers in Psychology, 2022)
Teachers have the main role in cultivating the future members of the community by their effort in the educational space and indeed the quality of education would not be accomplished without the ultimate determinations of enthusiastic and committed educators. Henceforth, there is a need for more investigation regarding the conception of teacher commitment, and the aspects that affect it. Educator commitment has an important function in influencing educators’ presentation; thus, it is necessary to determine the fundamental elements that contribute to educator commitment. Moreover, buoyancy is another fundamental construct in a psycho-educational environment helping people in academic challenges. Psychological health is another term considered as a significant dimension in an academic environment. The present review tries to focus on psychological health and buoyancy that affect educators’ job commitment using the theoretical agenda of Positive Psychology and the social-cognitive theory. Succinctly, this review of literature has implications for scholars, theorists, and practitioners seeking for inspecting the roles of buoyancy and psychological health on teachers’ professional commitment.